The 7 habits of highly effective people : powerful lessons in personal change - Covey. Stephen R.; Sean Covey (Contributor); James C. Collins (Ashland : Blackstone Publishing, 2023)
This beloved classic presents a principle-centered approach for solving both personal and professional problems. With penetrating insights and practical anecdotes, Stephen R. Covey reveals a step-by-step pathway for living with fairness, integrity, honesty, and human dignity
Includes index "Updated with fresh insights by Sean Covey" -- Page 1 of cover
Keywords: BUSINESS & ECONOMICS / Leadership; Character